The functional role of protein dynamics in photosynthetic reaction centers investigated by elastic and quasielastic neutron scattering - Pieper Jörg (EPJ Web of Conferences, 2015)
This short review summarizes our current knowledge about the functional relevance of protein dynamics in photosynthetic reaction centers. In the case of Photosystem II membrane fragments, elastic and quasielastic neutron scattering experiments reveal a dynamical transition at about 240 K corresponding to the activation of picosecond molecular motions. Likewise, a “freezing” of molecular dynamics is observed upon dehydration. Intriguingly, these effects correlate with the pronounced temperature- and hydration-dependence of specific electron transfer steps in Photosystem II indicating that molecular dynamics is an indispensable prerequisite for its function. Thus, electron transfer in Photosystem II appears to be a prototypical example for a dynamics-function correlation. Finally, the laser-neutron pump-probe technique is shown to permit in-situ monitoring of molecular dynamics in specific functional states of a protein in real time.